PREDIKSI TINGKAT PRODUKSI PADI DI LOMBOK BARAT DENGAN METODE LEAST SQUARE: Prediction of Rice Production Levels in West Lombok Using the Least Squares Method - Fitrawati, Elyin; Setiawati, Setiawati; Rahayu, Sri Puji; Robbaniyyah, Nuzla Af’idatur; Rusadi, Tri Maryono (Yayasan Al-Amin Qalbu, 2026)
Rice is one of the crops that plays a significant role in maintaining food security and supporting Indonesia’s economy. As the staple food for the majority of the population, rice strongly influences the country’s social and economic conditions. Due to its crucial importance, accurate predictions of rice production are required to support more effective planning. This study aims to forecast rice production in West Lombok Regency using the least square method. The data utilized include harvested area and rice production from 2011 to 2022. The resulting prediction model is a second-degree polynomial function that represents the relationship between harvested area and total rice production. Based on the Mean Absolute Percentage Error (MAPE) analysis, an error rate of 2.2391% was obtained, indicating that the model has a very high level of accuracy, as the error is below 10%. The findings of this study are expected to serve as a reference for more precise planning to improve rice production in West Lombok Regency